2023
DOI: 10.3390/nu15030751
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Trajectories of Body Mass Index and Waist Circumference and Their Associations with Hypertension and Blood Pressure in Chinese Adults from 1991 to 2018: A Prospective Study

Abstract: Body mass index (BMI) and waist circumference (WC) have been suggested to be involved in the etiology of hypertension. The present study aimed to determine multiple trajectories of BMI and WC, then examined their associations with the risks of hypertension and high blood pressure in Chinese adults. The study used China Health and Nutrition Survey data from 1991 to 2018. The sample included 9651 adults aged 18 years or older. We used group-based multi-trajectory modeling to identify trajectories. We estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
4
4
0
Order By: Relevance
“…This grouping can not only re ect the status of obesity and central obesity, but also show the baseline obesity level and long-term change trends simultaneously. To the best of our knowledge, only one study [24] reported multi-trajectory of BMI and WC, and its results were similar to our study. In addition, the BMI trajectories [25,26] and WC trajectories [27] derived from large samples of adults only also showed four increasing trend groups.…”
Section: Discussionsupporting
confidence: 90%
“…This grouping can not only re ect the status of obesity and central obesity, but also show the baseline obesity level and long-term change trends simultaneously. To the best of our knowledge, only one study [24] reported multi-trajectory of BMI and WC, and its results were similar to our study. In addition, the BMI trajectories [25,26] and WC trajectories [27] derived from large samples of adults only also showed four increasing trend groups.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous study reported that overexpression of RTN3 may partly lead to HTG and obesity, which are important factors in the development of secondary hypertension. 12 , 17 To further investigate the association between RTN3 and hypertension, we enrolled 18 healthy controls and 56 primary hypertension patients with normal triglyceride levels (<1.7 mmol/L) and body mass index (18.5–24 kg/m 2 ) to exclude the effects of HTG and obesity. Enzyme‐linked immunosorbent assay (ELISA) detection exhibited higher RTN3 levels in part patients (Figure 1A and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation is that, in this study, HTN classification by casual BP was based on a one-time measurement (average of two consecutive measurements), compared with 2–3 different visits to confirm sustained elevations in BP in clinical practice ( 56 ). However, this procedure is widely used in epidemiological studies, especially those with large sample sizes ( 57 59 ). Furthermore, HTN classification was used only in the descriptive analysis and casual BP levels were included as a secondary outcome in our study to compare results with multiple BP readings from ABPM over a 24-hour period.…”
Section: Discussionmentioning
confidence: 99%